Distance Education Practices During the COVID-19 Lockdown: Comparison of Belgium, Japan, Spain, and Türkiye - Akkan, Irem Nur; Eminoglu Kucuktepe, Seval (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
During the COVID-19 pandemic, many things changed in people’s educational lives as individuals transitioned to remote learning. While technologically advanced countries swiftly adapted to the new normal, less developed countries encountered substantial obstacles. This study aimed to compare distance education practices during the lockdown in four OECD countries (Belgium, Japan, Spain, and Türkiye) and provide future-oriented suggestions. A systematic literature review was conducted using OECD documents on distance education practices accessed through the OECD iLibrary database with a keyword search. Nine papers out of 1,294 meeting inclusion criteria were thoroughly reviewed, focusing on categories such as general information, sample practices, implementation challenges, conducting courses, supporting students during the lockdown, and evaluation and national examinations. A descriptive analysis was performed based on coding categories. Findings revealed that school closure durations varied by country and educational level, with each country adopting approaches suitable for distance learning. Online learning platform development was similar across countries, except for Japan, which has a distinct curriculum structure. Challenges, including technological limitations and resistance to change, were common, exacerbated by a lack of expertise and the need for rapid adaptation. Distance education primarily relied on computers, television, and homework, with radio use varying. Decision-making processes differed across countries, with centralized decision-making observed in Türkiye. Supporting disadvantaged students and addressing learning losses were prioritized, and national exams were postponed with changes in content and the number of questions.